The Greek Text of the Gospel of John According to the Early Papyri - Comfort, Philip W. (New Testament studies, 1990)
Out of all the NT books, the Gospel of John has the most witnesses among the papyrus MSS – twenty-two to date (P2, 5, 6, 22, 28,36, 39, 44, 45, 52, 55, 60, 63, 66, 75, 76, 80, 84, 90, 93, and 95). Two of these MSS, P66 and P75, contain a good portion of this gospel by themselves; and when all the MSS are compiled together, they cover nearly the entire book, with a great deal of overlap. The missing portions are as follows: 14. 31; 15.1; 16. 5, 8–10; 21.10–11, 14, 16, 21–22. Many more verses, especially in chapters 14–21, have lacunae.